Analysis of the aliasing effect caused in hardware-in-the-loop when reading PWM inputs of power converters. (March 2022) - Zamiri, Elyas; Sanchez, Alberto; Martínez-García, María Sofía; de Castro, Angel
Abstract: Hardware-in-the-loop (HIL) systems are commonly used to debug controllers in closed-loop operation. Therefore, the frequency response of the emulated subsystem is of special relevance. Undesirable oscillations can appear as a consequence of digitally sampling the switch control signals in power converter HIL models. These oscillations at relatively low frequencies, below the switching frequency, may confound the closed-loop operation and, therefore, the appropriate debugging of the controller. This paper shows that the lost information when an HIL model reads a PWM signal may create some output offset error or steady-state fluctuations, especially when the switching period and the sampling step get closer. The aliasing frequencies produced by the input sampling are calculated, and the small-signal analysis explains the relation between the output oscillation and the input PWM sub-harmonics. The output error spectrum proves that the main error sub-harmonics have the same aliasing frequency components. Both captured oscilloscope results obtained by an NI myRIO device and MATLAB simulations verify that significant distortions can be seen in the output inductor current if there is a low aliasing frequency in the digital version of the input PWM signal read by the HIL model. Highlights: Aliasing effect caused by digitally sampling the PWM signal in HIL models. Sub-harmonic oscillations HIL models caused by aliasing when sampling PWM signals. Analysis of the switching and sampling periods in the sub-harmonic oscillations. A detailed analysis of the spectrum of digitally sampled PWM signals. MATLAB simulation and experimental results using an NI myRIO device.